How to draw a virtual cubical perspective box - Araújo, António (2022)
In this workshop we will learn how to draw a cubical perspective by hand and how to visualize the resulting drawing as a VR panorama, creating a kind of virtual perspective box. We will do this by viewing cubical perspective as a special case of spherical perspective and considering how spherical geodesics project on the cube.